Epidemiological, Clinical, Bacteriological, and Therapeutic Aspects of Sur-gical Site Infections in the Maternity Ward of the Batna Region, Algeria: A Prospective Study - DJAARA, Hayat; charif , Chahrazad; Benbrahim, Chahra zed (Universitas Airlangga, 2025)
Surgical site infections (SSIs) are nosocomial infections occurring after surgery. SSIs contribute to the increase in maternal morbidity associated with cesarean section (CS). This research aimed to study SSIs' clinical, epidemiological, bacteriological, and therapeutic aspects for cesarean and hysterectomy surgeries performed at the Maternity Hospital of Batna Region in Algeria. We carried out a prospective and descriptive study for four months (from 1 January 2018 to 30 April 2018), with real-time data collection, in the gynecology and obstetrics department of Batna’s Maternity Hospital. We included a total of 24 women who had a surgical intervention and were hospitalized with post-surgical infection. The data collection using a questionnaire allowed us to obtain information concerning the patient and the surgical procedure. Our results show that most surgeries performed were CS (95.83%) compared to hysterectomies (4.16%), among which 54.16% were planned CS. All classes of contamination were clean-contaminated. The physical status score for American Society of Anesthesiologists (ASA) 1 and ASA 2 classes was found in 83.33% and 16.66% of the patients, respectively. The SSIs in this study were concerned mainly with the surface plane (95.83%). Concerning infection, pus samples were taken from ten patients, and five germs were identified in eight patients. Escherichia coli was isolated in three patients, and Proteus mirabilis in two patients. Serratia marcescens, Acinetobacter baumanni, and Burkholderia cepacia were identified once in the three remaining patients. The most commonly prescribed antibiotherapy was Metronidazole (95.83%). We established a clinical, epidemiological, bacteriological, and therapeutic profile for SSIs at the Maternity Hospital of Batna.